Development of Biofertilizer from Locally Sourced Materials - Mujahid Umar Yunus; Kiman Silas; Ali L. Yaumi; Bitrus Highina Kwaji (CV. Literasi Indonesia, 2023)
The appropriate rationing of NPK is a core problem in biofertilizer production. In this study, a 30-liter bench-scale anaerobic biodigester for biofertilizer production from solid waste was fabricated using galvanized steel sheet. About 4kg of chicken dung, 7.5 kg of wastewater treatment sludge, and 0.5 kg of banana peel are mixed, a total of 12kg, the substrate is then mixed with water in a ratio of 1:1. (w/w) 24 kg of the slurry is fed into the biodigester. The slurry is allowed to stay for 37 days at mesophilic temperature. The pH of the digestion is between 6-7, and the temperature is within the range of 25-34oC. The amount of total solid, moisture content, ash, and volatile matter of the feedstock after digestion decreases by about 31%,47%,67%, and 69%. Moreover, an increase in the amount of nitrogen content from 0.3783% to 0.6420%, phosphorous from 0.1903% to 0.2983%, and potassium from 0.1876% to 0.3153% was also observed. After digestion the biofertilizer produced has an appropriate ratio of 2:1:1. For the kinetic study, the specific growth was found to be 0.0098hr-1. Also, experimental data for microbial growth obtained from the study fitted the Monod model.